Comorbidity Patterns in Chronic Obstructive Pulmonary Disease and Their Associations with Service Utilization - Yanran Duan; Hang Fu; Changying Chen; Yaojun Zhao; Shuai Jiang; Chengzeng Wang (COPD)
Background The prevalence of combinations of comorbidities and their associations with inpatient service utilization and readmission among patients with chronic obstructive pulmonary disease (COPD) have not been extensively examined. To address this gap in knowledge, an observational prospective study was conducted using retrospective data.Aims To identify patterns of comorbidities linked to length of hospital stay, daily expenses, and one-year readmission.Methods The 30 most common comorbidities were identified in patients with secondary diagnoses using the association rule mining (ARM) method. Regression models were used to examine the relationships between combinations of comorbidities and service utilization, with adjustments for covariates.Results The five most prevalent comorbidities were pulmonary heart disease (40.99%), ischemic heart disease (38.97%), heart failure (36.77%), hypertension (34.11%), and respiratory disorders (19.12%). Most combinations of comorbidities identified by ARM showed significant associations with an extended length of stay (>13 days), increased daily expenses (>930 CNY), and reduced readmission rates. Among these combinations, glycoprotein metabolism disorder had the strongest association with prolonged length of stay (adjusted odds ratio [aOR]): 1.89, 95% confidence interval [CI]: 1.82–1.95). Conversely, the combination of other brain diseases and respiratory failure was linked to higher daily expenses (aOR: 11.34, 95% CI: 10.58–12.15), and the presence of pulmonary heart disease was associated with elevated one-year readmission rates (aOR: 1.41, 95% CI: 1.37–1.46).Conclusion Common combinations of comorbidities among inpatients with COPD were identified from an extensive collection of discharge medical records. Furthermore, the associations between comorbidities, inpatient service usage, and readmission rates were determined.